2018
DOI: 10.1186/s12936-018-2337-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity and molecular epidemiology of Plasmodium vivax and Plasmodium falciparum infections in East Africa

Abstract: BackgroundParasite genetic diversity and multiplicity of infection (MOI) affect clinical outcomes, response to drug treatment and naturally-acquired or vaccine-induced immunity. Traditional methods often underestimate the frequency and diversity of multiclonal infections due to technical sensitivity and specificity. Next-generation sequencing techniques provide a novel opportunity to study complexity of parasite populations and molecular epidemiology.MethodsSymptomatic and asymptomatic Plasmodium vivax samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 78 publications
(83 reference statements)
6
37
1
Order By: Relevance
“…In 2018, Zhong et al . reported the prevalence of polyclonal infections to be 75% in western Kenya . This was a slight reduction from the ≥ 80% prevalence reported by previous studies .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In 2018, Zhong et al . reported the prevalence of polyclonal infections to be 75% in western Kenya . This was a slight reduction from the ≥ 80% prevalence reported by previous studies .…”
Section: Discussioncontrasting
confidence: 59%
“…Unexpectedly, we observed a lower proportion of polyclonal infections (51%) than previously reported in western Kenya. In 2018, Zhong et al reported the prevalence of polyclonal infections to be 75% in western Kenya [37]. This was a slight reduction from the ≥ 80% prevalence reported by previous studies [13,14,19,38].…”
Section: Discussionmentioning
confidence: 88%
“…In most of its geographic range, P. vivax showed high levels of genetic diversity as revealed by population genetic studies using various genotyping markers [12][13][14][15][16][17][18][19][20][21]. Paradoxically, even in many low transmission settings, P. vivax still maintains high levels of diversity [22][23][24][25][26]. As a result, in areas of P. vivax and P. falciparum co-endemicity, these two parasites tend to exhibit markedly different genetic diversity and population structures, with P. vivax showing more stable transmission patterns [14,15,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the prevalence of deletions in pfhrp2 gene found in each individual study could be higher and generally the malaria infections are polyclonal in SSA and Indian endemic regions [64][65][66]. It is likely that individuals are infected with both malaria parasites with deletions in pfhrp2 gene and without deletions wherein, the presence of malaria parasites with no pfhrp2 deletions can overshadow that of their counterparts with deletions in pfhrp2 gene.…”
Section: Discussionmentioning
confidence: 93%